510. Elevated IL-1β level as a predictor of inflammation and death in COVID-19. (31st December 2020) - Swartz, Talia H; Gnjatic, Sacha; Aberg, Judith A; Merad, Miriam; Sigel, Keith
Abstract: Background: SARS-Cov-2 (severe acute respiratory disease coronavirus 2) causes Coronavirus Disease 2019 (COVID19) and is associated with respiratory failure and death in severe disease. This is associated with high levels of cytokines such as IL-6, IL-8 and TNF-alpha which are predictors of severe outcomes. SARS-CoV-2 leads to activation of the NLRP3 inflammasome which results in secretion of the cytokine IL-1ß. While high levels of IL-1ß are not observed in most patients with severe COVID-19, there is a subset of patients with high IL-1ß levels. Here we sought to characterize these patients and determine whether high IL-1ß levels are associated with adverse outcomes and death in COVID-19. Methods: We identified 90 patients with high IL-1ß levels (greater or equal to 2 pg/ml) and laboratory confirmed COVID-19 hospitalized in our hospital system in New York March 12 and May 8, 2020. We collected baseline clinical characteristics, laboratory values, COVID-19 treatment, and outcomes from this group and the group with IL-1ß levels below 2 pg/ml. Baseline clinical characteristics and outcomes were compared. Results: Comparing patients by IL-1ß level had similar demographics (age, sex, race/ethnicity, smoking status and comorbid disease prevalence). The group had comparable levels of adverse markers of disease severity but the patients with high IL-1ß had increased inflammatory biomarkers including IL-8 (629 vs. 68 pg/ml, p< 0.0001), TNF-alpha (30 vs. 51 pg/ml, p< 0.0001), IL-6 (173 vs. 5075 pg/ml, p< 0.0001), CRP (141 vs. 178, p=0.0007), d-dimer (2.6 vs. 4 p=0.0002), and increased rates of death (30% vs. 20%, p=0.008). Conclusion: Demographic and comorbid conditions are not effective at predicting high IL-1ß serum levels in COVID-19 patients, however those individuals with high levels are at risk for adverse outcomes of severe disease and death. Further investigation is required to probe the mechanism of NLRP3 inflammasome activation and IL-1ß signaling and the role of this cytokine in mediated inflammation and death in COVID-19. Disclosures: Judith A. Aberg, MD, Theratechnology (Consultant)